Evaluation of selected physico-chemical, colour and textural characteristics of market Gulabjamun - Sukre, Vivekanand Natha; Barnwal, Pradyuman; Chavhan, Bhavesh B; Deep, Ankit; Bhagat, Pooja N (Indian Journal of Dairy Science, 2021)
Gulabjamun is one of the most popular traditional Indian dairy products. The various characteristics such as physico-chemical, colour and textural quality characteristics of six brands of Gulabjamun were investigated which plays important role in its marketing and consumer acceptance. The fat and unit-weight of market Gulabjamun were found statistically highly significantly different (p<0.01). The moisture content, percent absorbed sugar, GMD, sphericity of market Gulabjamun were found statistically highly significant (p<0.001). Apparent density was statistically significant (p≤0.05). The fat, moisture and percent absorbed sugar of market Gulabjamun were ranged between 6.47±0.37 to 12.32±1.19 %, 40.51±0.70 to 47.53±0.42 % d.b. and 12.24±0.25 to 37.65±0.52%, respectively. The geometrical mean diameter, apparent density and unit-weight varied between 3.09±0.01 to 3.60±0.06 cm, 1.40±0.05 to 1.84±0.32 g/cm3 and 24.21±0.29 to 44.40±0.45 g, respectively. Colour characteristics i.e. L*, a*, b* and browning index (BI) market Gulabjamun were found statistically highly significant (p<0.001). The variation in the values of L*, a*, b* and brownness index was observed to be between 34.70±0.41 to 46.46±0.55, 3.92±0.28 to 6.50±0.39, -2.30±0.59 to 11.48±0.48, and 2.77±1.33 to 36.98±0.56, respectively. The hardness, cohesiveness, gumminess, chewiness and resilience were found statistically highly significant (p<0.001) whereas springiness was found statistically non-significant (p˃0.05). The hardness, springiness, gumminess, chewiness, cohesiveness and resilience ranged between 3.36±0.56 N to 10.71±1.66 N, 0.52±0.29 to 0.88±0.12, 0.86±0.13 N to 2.14±0.28 N, 0.44±0.24 N to 1.88±0.30 N, 0.18±0.01 to 0.25±0.01 and 0.24±0.01 to 0.35±0.02, respectively. It was observed that the size of market Gulabjamun (3.09±0.01 to 3.60±0.06 cm) may be taken as 3.0-3.6 cm for development of process equipments for Gulabjamun manufacturing.